From SEMP to SEMS to SEMS II. Issue 3 (29th April 2013) - Sutton, Ian
<x xml:space="preserve">Abstract</x> This article describes the new offshore safety management rule that is often referred to as SEMS II. © 2013 American Institute of Chemical Engineers Process Saf Prog 32: 311–312, 2013